2021
DOI: 10.1016/j.heliyon.2021.e07774
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of TAP block versus ilioinguinal block for post-cesarean section pain management: A systematic review and meta-analysis

Abstract: Background Controversy still exists regarding the analgesic efficacy of transverse abdominis plane (TAP) block versus ilioinguinal or iliohypogastric (IL/IH) nerve block for postoperative pain management following cesarean section. This meta-analysis aimed to perform relatively credible pooled results on the efficacy of the TAP versus IL/IH nerve block for postoperative pain management after cesarean section. Methods Databases such as: PubMed/MEDLINE, Google scholar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…El bloqueo TAP ha demostrado ser efectivo reduciendo el dolor, reduciendo el consumo de analgesia de rescate y con satisfacción de las gestantes [19] así como también el bloqueo de los nervios ilioinguinal e iliohipogástrico se combinan con bloqueos TAP, se obtiene una mejor analgesia y se reduce la necesidad de opiáceos de rescate [19], [22].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El bloqueo TAP ha demostrado ser efectivo reduciendo el dolor, reduciendo el consumo de analgesia de rescate y con satisfacción de las gestantes [19] así como también el bloqueo de los nervios ilioinguinal e iliohipogástrico se combinan con bloqueos TAP, se obtiene una mejor analgesia y se reduce la necesidad de opiáceos de rescate [19], [22].…”
Section: Discussionunclassified
“…Los nervios ilioinguinal e iliohipogástrico están contenidos en un plano tisular bien definido entre el transverso del abdomen y los músculos oblicuos internos [19] (Figura 4).…”
Section: Bloqueo Ilioinguinal/iliohipogastricounclassified
“…[50][51][52][53] A systematic review of 5 RCTs found similar efficacy for post-cesarean analgesia when comparing midaxillary TAP blocks to II/IH blocks. 62 Two meta-analyses of postcesarean patients in the absence of neuraxial morphine were unable to find significant analgesic advantage to an ultrasound guided TAP block versus direct wound infiltration of local anesthetic in the subcutaneous tissue by the surgeon. 63,64…”
Section: Efficacy In Cesarean Analgesiamentioning
confidence: 99%
“…Under the guidance of ultrasound, the distribution and course of peripheral nerves, as well as the surrounding blood vessels and organs, can be observed, and the puncture localization is accurate, which avoids stray into blood vessels, thoracoperitoneum, and important organs. Moreover, the injection and diffusion process of local anesthetics can be observed, reducing the amount of local anesthetics, and the block effect is obvious and lasts for a long time ( 10 , 11 ). Nerve block by ultrasonography can block multiple small nerves or plexuses to achieve regional anesthesia and analgesia through the diffusion of local anesthetics in the musculofascial plane.…”
Section: Introductionmentioning
confidence: 99%
“…Figure11 Funnel plot of the effect of nerve block on pain events after ultrasonography. SE, standard error; OR, overall risk.…”
mentioning
confidence: 99%